2014
DOI: 10.1144/petgeo2013-041
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum column-height controls in the western Hammerfest Basin, Barents Sea

Abstract: Hydrocarbon leakage is a major exploration challenge in the western Hammerfest Basin. Most exploration failures in the area have been attributed to leakage; hydrocarbon-bearing traps are rarely filled to their structural capacity, and almost all traps have hydrocarbon shows down to their structural spillpoint or below. We have investigated to what extent the hydrocarbon column heights can be explained by vertical leakage along faults or at fault intersections. For the fields that we evaluated we obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The top of the shallowest structure in a strongly overpressured cell is closest to the fracture pressure and most likely to vent, unless there are weak areas in the cap rock at other locations. Hermanrud et al (2014) concluded that leakage rates in the hydrostatic system in the Hammerfest Basin were higher from areas where the seal is weakened by fault intersections. Since overpressures in the strongly overpressured regime are preserved, it must be assumed that venting takes place over a geological timescale.…”
Section: The Strongly Overpressured Regimementioning
confidence: 99%
“…The top of the shallowest structure in a strongly overpressured cell is closest to the fracture pressure and most likely to vent, unless there are weak areas in the cap rock at other locations. Hermanrud et al (2014) concluded that leakage rates in the hydrostatic system in the Hammerfest Basin were higher from areas where the seal is weakened by fault intersections. Since overpressures in the strongly overpressured regime are preserved, it must be assumed that venting takes place over a geological timescale.…”
Section: The Strongly Overpressured Regimementioning
confidence: 99%
“…Based on hydrocarbon flow lines and catchment areas (Figures 9 and A5), the hydrocarbons migrate to the western edge of the Snøhvit field and are controlled by the faults and their intrinsic properties (FCP and permeability). In the Askeladd field (Figure 1), dry structures are thought to result from leakage of hydrocarbons along the junctions between several first order fault intersections [86]. The fault networks above the Snøhvit field form a dense network of deep first order tectonic faults (Figures 3 and 5), linking the Paleocene-Early Eocene strata with the underlying Jurassic reservoirs and second order faults ( Figure 5), which are sealed below the Early Cretaceous [17].…”
Section: Leakage and Accumulation In Shallow Trapsmentioning
confidence: 99%
“…Jurassic to Early Cretaceous rifting established classic rotated fault blocks and horst structures, which have been the main targets for early exploration (Gabrielsen et al 1990;Faleide 2008;Hermanrud et al 2014).…”
Section: Ssw Activation Of Both High-angle Normal Faults and Listricmentioning
confidence: 99%
“…Negative effects of the Cenozoic uplift event have been largely blamed for disrupting the petroleum system. Issues such as reactivation of faults, erosion of top seal, gas expansion, differential tilting, secondary migration and cooling of source rocks have all been proposed as causing depleted targeted reservoirs (Doré 1995;Doré & Jensen 1996;Doré & Lundin 1996;Duran et al 2013;Hermanrud et al 2014;Ostanin et al 2017).…”
Section: Ssw Activation Of Both High-angle Normal Faults and Listricmentioning
confidence: 99%